Upaya Meningkatkan Kemampuan Motorik Kasar Anak Usia Dini Melalui Gerak Lokomotor - Narlina; Laili Etika Rahmawati (UIN Raden Mas Said Surakarta, 2024)
One of the children's development that must be improved is gross motor. Locomotor motion is an activity that can improve gross motor. The purpose of the study was to improve children's gross motor through locomotor motion at TK Aisyiyah Bustanul Athfal IV Sunggingan. The research methodapplied in this study is classroom action research. This class action research is carried out in two cycles. Each cycle carries out four main activities, namely planning, implementation, observation, and reflection. Based on the description of the results of research carried out in cycle I and cycle II, it can be concluded that gross motor skills through locomotor movement activities in group B children of Aisyiyah Bustanul Athfal IV Kindergarten increased. This can be proven from the data from observations in each cycle. The average result in the pre-cycle presentation only reached 54% Then in cycle I the average presentation increased to 73% and the average percentage in cycle 2 increased to 93%. The increase from pre-cycle to cycle I is 19% and the increase from cycle II to cycle 2 is 20%.